Corrosion control for offshore structures cathodic protection and high-efficiency coating - Singh, Ramesh (Gulf Professional Publishing, 2014)
Annotation
Includes bibliographical references and index. - Print version record
Keywords: Offshore structures -- Corrosion; Corrosion and anti-corrosives; Corrosion; Structures offshore; Corrosion; corrosion (condition changing process); Offshore structures; Corrosion